Management of Mycobacterium tuberculosis Prosthetic Joint Infection: 2 Cases and Literature Review. (31st August 2021) - Lo, Carson K L; Chen, Lina; Varma, Sonal; Wood, Gavin C A; Grant, Jennifer; Wilson, Evan W
Abstract: Prosthetic joint infection caused by Mycobacterium tuberculosis (TBPJI) is uncommon but can be encountered in immunocompromised patients or those from tuberculosis-endemic regions. A lack of clinical suspicion and experience with TBPJI often leads to a delay in diagnosis. We report 2 cases of TBPJI in a Hungarian-Canadian and Iranian-Canadian immigrant, respectively. Both were treated with concurrent surgical and medical therapy. We also performed a literature review on TBPJI case reports, outlining their diagnosis and management.